A new acid isolated from V. negundo L. inhibits NLRP3 inflammasome activation and protects against inflammatory diseases - Di, Qianqian; Zhao, Xibao; Lin, Jing; Li, Xunwei; Li, Xiaoli; Tang, Haimei; Zhang, Ruihan; Xiao, Weilie; Chen, Weilin (Frontiers in Immunology, 2023)
The NLRP3 inflammasome plays a critical role in the innate immune response, and its excessive activation will cause pyroptotic cell death and be associated with the onset of inflammatory diseases. However, NLRP3 inflammasome targeting therapies are still to be implemented in the clinic setting. Here, we first isolated, purified and characterized a novel Vitenegu acid from V. negundo L. herb that specifically inhibits NLRP3 inflammasome activation, without affecting NLRC4 or AIM2 inflammasomes. Vitenegu acid blocks the oligomerization of NLRP3, thus inhibiting NLRP3 inflammasome assembly and activation. In vivo data show that Vitenegu acid exerts therapeutic effects on NLRP3 inflammasome-dependent inflammation. Taken together, our results suggest that Vitenegu acid is a candidate therapeutic agent for treating NLRP3 inflammasome related diseases.